Information and Entertainment Channels at Underground and Buses Systems in Spain - Mena Muñoz, Sergio; Martínez Fernández, José Luis (Estudios sobre el Mensaje Periodístico, 2012)
The possibilities of development of information technologies have made possible the union of two such disparate areas as transportation and media. Now it is possible to enjoy a television channel sitting on the seat of public transport, something unthinkable twenty years ago. This opens up a field full of possibilities for managers, responsibles for the content and for advertisers, who have at their disposal a captive audience never before considered who may rebel against the interference of their public space. This article researches the characteristics, possibilities and the impact produced by the launch of two media channels in Madrid and Barcelona Underground and city buses in some Spanish cities.